2010
DOI: 10.1111/j.1365-3156.2010.02486.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding why patients with cataract refuse free surgery: the influence of rumours in Kenya

Abstract: Summaryobjectives To understand the reasons that hinder people from uptake of sponsored cataract surgery. methods A mixed methods (qualitative and quantitative) approach was used. During routine screening activities at Kwale District, Kenya, local residents with visually impairing cataract were clinically assessed and offered free surgery. Interviews were conducted using a semi-structured guide that covered different aspects related to acceptance of cataract surgery including knowledge of others who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 13 publications
0
32
1
Order By: Relevance
“…5 This encouraging change can be attributed to the significant changes made at Nkhoma based on the Vision 2020 cataract services management principles for cataract case finding and improving efficiency of service delivery. 12 This increase in cataract surgery output has been achieved by active case finding; partnership with local community-based rehabilitation program, MACOHA (Malawi Council for the Handicapped), and constant support from an international NGO allowing free hospital arranged transport, accommodation and surgery. Internal management changes also ensured higher efficiency in utilizing available infrastructure and human resources.…”
Section: Discussionmentioning
confidence: 99%
“…5 This encouraging change can be attributed to the significant changes made at Nkhoma based on the Vision 2020 cataract services management principles for cataract case finding and improving efficiency of service delivery. 12 This increase in cataract surgery output has been achieved by active case finding; partnership with local community-based rehabilitation program, MACOHA (Malawi Council for the Handicapped), and constant support from an international NGO allowing free hospital arranged transport, accommodation and surgery. Internal management changes also ensured higher efficiency in utilizing available infrastructure and human resources.…”
Section: Discussionmentioning
confidence: 99%
“…From experience, old age, a poor prognosis and fear are some of the reasons why some patients or their families decline to provide consent for surgical operations. In Kenya, Briesen et al reported that the rumour that those who had cataract surgery would be blind prevented many people with cataract from consenting for free surgery 14. However, it was discovered during interview of these patients that none of them had actually seen anyone blind after surgery but that they heard about it from people who also had heard about it from other people.…”
Section: Discussionmentioning
confidence: 99%
“…[33] While this is only one of several reasons for refusing surgery it is important for service providers to maximize good outcomes so rumors such as this are minimized.…”
Section: Why Is Poor Outcome After Cataract Surgery An Important Issue?mentioning
confidence: 99%